Cushing's disease: Current trends in treatment - Juszczak, A; Grossman, AB (2013)
Cushing's disease (CD) is an uncommon endocrine disorder resulting from an adrenocorticotrophin-producing pituitary adenoma. Its clinical features and subsequent comorbidities are the consequence of hypercortisolism and may be life-threatening if untreated. Trans-sphenoidal selective adenomectomy or hypophysectomy remain recommended first-line treatments for CD and may be repeated if unsuccessful or following recurrence of the tumor. Pituitary radiotherapy, either conventional fractionated external beam or in the form of radiosurgery, is a second-line treatment option, but its effects are delayed for several years. Bilateral adrenalectomy is a valuable treatment option for acutely unwell patients or for those who are unable to take or tolerate medical therapy. Steroidogenesis inhibitors such as metyrapone, ketoconazole, etomidate and mitotane have their place at many stages in the management of CD and are usually very effective. Pituitary tumor-targeted agents, such as cabergoline or pasireotide, remain as second-line medical treatment options, but are effective in only some 25-30% of patients. © 2013 Future Medicine Ltd.